TECHNICAL ANALYSIS: THE ROLE OF INVESTOR PSYCHOLOGY MEDIATING ON STOCK INVESTMENT BEHAVIOR - Asmilia, Nur (Universitas Pamulang, 2019)
The purpose of this study is to prove empirically whether the technical factors represented by stock price indicators, trading volume and market capitalization have an influence on investor psychology. In addition, it is also to determine the effect of investor psychology on the behavior of stock investment. The number of data samples in this study that is as many as 108 respondents from the population of investors who have been chosen as the object of research. The sampling technique in this study is random sampling. The use of the technique is due to the population that is unknown to the researcher. Testing the hypothesis is tested by structural equation modeling. The results showed that stock prices, trading volume and market capitalization have a significant influence on investor psychology, and investor psychology is known to have a significant effect on stock investment behavior